The promise of tirzepatide: A narrative review of metabolic benefits - Sara Sokary (17337724) (2025)
Obesity and type 2 diabetes mellites (T2DM) are intertwined epidemics that continue to pose significant challenges to global public health. We aim to review the available evidence on the metabolic effects of tirzepatide, focusing on weight loss and maintenance of lost weight, body composition alterations, appetite regulation, glycemic control, and lipid profile modulation. Tirzepatide administration for 72 weeks elicited significant weight reduction ranging from 5 % to 20.9 % across different trials in a dose-dependent manner. Furthermore, limited evidence showed that lost body weight may be primarily due to fat mass reduction. Tirzepatide also significantly decreased food intake, reduced overall appetite scores and increased fasting visual analog scale scores for satiety and fullness across different clinical trials. Moreover, tirzepatide exhibited favorable effects on glycemic control, with notable reductions in HbA1c levels ranging from 20.4 mmol/mol with the 5 mg dose to 28.2 mmol/mol with the 15 mg dose, following treatment durations lasting 40–52 weeks. Additionally, tirzepatide exerts a beneficial impact on lipid profile parameters, including reductions in total cholesterol, low-density lipoprotein cholesterol, and triglyceride levels, while increasing high-density lipoprotein cholesterol concentrations. Despite its efficacy, tirzepatide is associated with gastrointestinal adverse effects, which requires dose escalation strategies to enhance tolerability. Mild to moderate adverse events are commonly reported at higher doses, with discontinuation rates ranging from 4 % to 10 % across different dosages. In conclusion, tirzepatide has shown multifaceted metabolic effects, along with manageable adverse profiles, which makes it a promising therapeutic agent for addressing both obesity and T2DM. However, further long-term randomized controlled trials are warranted to reveal long-term efficacy and safety outcomes, particularly in diverse patient populations. Other Information Published in: Primary Care Diabetes License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pcd.2025.03.008